Business Simulation, Student Competency, And Learning Outcomes - Christiana Fara Dharmastuti; Syarief Darmoyo; Reinandus Aditya Gunawan; Maria Natasya Duka (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The shifting paradigm in the learning process changes with technological advances and the internet. The learning process is through conventional classes with teacher centre learning and is changing towards student centre and experiential learning. Unika Atma Jaya's management program develops learning using IT platforms for business simulations to train students' way of thinking about business processes within the company virtually. This study wants to examine how a business simulation class student's experience impacts student business competency and learning outcomes in learning Business Simulation. The results showed that student experience through perceived usefulness and perceived enjoyment affected learning outcomes mediated by student business competency.